Social movements and democratization in Malaysia - Khoo, Ying Hooi (2014)
The mixture model of democracy and authoritarian political system of Malaysia has long been said to hinder the social movements to expand their influence. However the wave of mass demonstrations in Malaysia with the emergence of an electoral reform movement, the Coalition for Clean and Fair Elections (Bersih) has attracted much political attention to the electoral politics in Malaysia, nationally and internationally. The emergence and the impact of social movements have been widely researched from a variety of perspectives especially in the Western world. However scholarship on social movements and protests in Malaysia remains limited. This thesis asserts that the area of social movements’ impact tends to be ignored in the process of political change in Malaysia. Therefore the key task for this thesis is to examine whether the social movements could influence the development of democracy in Malaysia. To do so, this thesis assesses the relevance of the political opportunity framework for social movements by applying it to the Bersih movement. The qualitative approach was chosen because of the interest of this thesis in the depth of the phenomenon of political change and how the Bersih movement has impacted to Malaysia’s political landscape. To achieve such purpose, this thesis applies the approaches of in-depth interviews, protest event analysis and participant observation. This thesis too considers the secondary sources. This thesis makes three key findings. First, the changing external opportunities provide political resources to Bersih movement that further on transform the political landscape in Malaysia. Second, the citizens’ political participation has increased and social movement spillover takes place. Third, the power dynamics between the opposition political parties and Bersih has been found to be particularly important factor in shaping the sequence and the outcome of the process as a whole. This thesis sheds light on the relationship between the social movement activity and democratic openness in an electoral authoritarian regime. At the same time a good base for protest movement analyses in the country, which has become a norm.